Deranged liver enzymes in type 2 diabetes mellitus subjects in a tertiary Malaysian hospital - Chellappah Thambiah, Subashini; Ramley, Nor Shaibah; Ghazali, Nur Syazwani; Ng, Ooi Chuan; Samsudin, Intan Nureslyna; Zahari Sham, Siti Yazmin (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: The prevalence of diabetes mellitus (DM) in Malaysia is drastically increasing. Subjects with DM are more likely to have deranged liver function tests (LFT). This study aimed to determine the prevalence of abnormal liver enzymes [(alanine aminotransferase (ALT) and alkaline phosphatase (ALP)] and its associated factors among type 2 DM (T2DM) subjects visiting a referral diabetic clinic in a tertiary government hospital. Methods: This retrospective, cross-sectional study included electronic data of 300 T2DM subjects ≥18 years old in the outpatient specialist clinic from January 2011 to December 2014. Statistical analysis was performed using SPSS version 22. Results: The study population at large included Malays, of age >60 years with comparable gender percentage. Most subjects had long-standing DM, poor glycaemic control and were on treatment. The prevalence of abnormal ALT and ALP was 27.3% and 13%; with 90.2% and 97.4% having mild ALT and ALP elevations, respectively. Significant associations noted for age, body mass index (BMI) and duration of T2DM for ALT whereas for ALP, anti-diabetic medication was significant between groups of normal and abnormal levels. Deranged liver enzymes were associated significantly with dyslipidaemia. Conclusion: Our study on the crude prevalence of raised liver enzymes may help identify T2DMpatients at increased risk of non-alcoholic fatty liver disease (NAFLD). Modification of metabolic risk factors, such as weight loss, control of dyslipidaemia rather than just tighter glycaemic control should be emphasised to reduce morbidity and mortality. Liver enzymes remain a simple and non- invasive marker of liver pathology in daily medical practice.